Comparison of Criminal Justice Systems Between Indonesia and Malaysia Regarding Sexual Violence - Graciela Natasha Lektonpessy; Irfa Ronaybod (Universitas Negeri Surabaya, 2024)
Sexual violence is a crime that is a problem throughout the world, especially in Indonesia due to several factors such as politics, poverty, patriarchal culture and the difficulty of handling cases of sexual violence that are sensitive for the victim. This is also experienced by Malaysia, which is a neighboring country of Indonesia and has similar conditions to Indonesia. Malaysia in addressing sexual violence in its country built the Anti-Sexual Harassment Tribunal which is quite unique and different from other countries from Indonesia, then a study was formed that will compare the rules regarding the criminal justice system and protection of victims in it related to the crime of sexual violence between Indonesia and Malaysia, using a legislative and comparative approach. This study will look at the comparison of these two countries in responding to cases of sexual violence with the regulations that have been made and implemented, as well as looking at the efforts of each country to improve the protection of victims of sexual violence from the regulations in their respective countries categorized by the Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power indicators.